Densidade nutricional para codornas japonesas em crescimento e postura - Silva, Ana Paula Bernardino da (2017)
Due to the needs of nutritional requirements values for Japanese quails in tropical conditions, research has been carried out throughout the national territory and, currently, there are tables of requirements elaborated in Brazil (Silva and Costa, 2009, Rostagno et al., 2011; Silva et al., 2012). In this scenario, the data compiled in the tables should be tested under the most different conditions, in order to evaluate their adequacy for the elaboration of efficient feeding programs according to each productive phase. Thus, it is necessary to study nutritional levels, to develop more technically adequate feeding programs, aiming at obtaining more consistent results, referring to production and nutritional requirements, aiming at the adoption of correct feeding programs, since approximately 75% of the cost Of poultry production comes from food. An experiment was carried out with the objective of evaluating the nutritional density of the diets on the production parameters of Japanese quails in all stages of development, divided into three phases: initial, growth and posture. In experiment I (1-21 days of age), 600 quails with one day of age and initial weight of (7 ± 0,2g), were distributed in 5 treatments with 8 replicates of 15 birds per replicate. In experiment II (22-42 days of age), the birds used were the same as those of experiment I, considering mortality and the birds withdrawn for slaughter, distributed in 5 treatments with 8 replicates according to the number of birds that remained in each portion. In experiment III, 320 quails were used in the same treatments with 8 replicates of 8 birds each replicate. Treatments consisted of rations with variation in nutritional density, with increments and decreases of 5 and 10% considering a basal diet. For the initial and growth phase, the performance variables were evaluated, such as feed intake (g / bird), final weight (g / bird), weight gain (g / bird), and feed conversion (g / g). In the laying phase the variables evaluated were: feed intake (g / bird), egg production (%), egg weight (g), egg mass (g), mass conversion (kg of feed / kg of egg ), Feed conversion per dozen eggs (kg of feed / dozen eggs), weight and percentage of bark, albumen and yolk (g); Thickness of bark (mm), specific gravity (g / cm³), Haugh unit, color of the yolk. Data were submitted to analysis of variance and analysis by polynomial regression. For the performance results of 1-21 and 22-42 days, weight gain and feed conversion were affected with nutritional densification, in which the birds responded better to the higher nutritional level. In the laying phase, egg production, egg weight, egg mass, conversion by mass and per dozen eggs, bark thickness and percentage of bark were affected by nutritional densification. The nutritional density influences the performance of Japanese quails, and up to 110% of nutrient content in the growth phase of poultry is recommended. While in the initial phase of posture the recommendation is 97%, that is, 3% less than recommended. In the final phase of the recommendation the recommendation is 104%, in this case 4% more of the recommendations. The nutritional requirements of the birds vary according to the production phase, being bigger in the growth phase.